Taxonomic revision of Guapinannus Wygodzinsky, 1951 (Hemiptera: Schizopteridae), with description of 19 new species - Frankenberg, Sarah; Knyshov, Alexander; Chamberlain, Rochelle Hoey-; Weirauch, Christiane (Zootaxa, 2021)
Guapinannus Wygodzinsky, 1951 (Hemiptera: Schizopteridae) was described based on a single female specimen from Costa Rica. Some additional specimens representing this genus have since become available and were incorporated into a comparative male genitalic study across Dipsocoromorpha and into combined molecular and morphological hypotheses of the infraorder. However, the species-level diversity of Guapinannus has remained unexplored and undocumented. Based on examination of 264 specimens from central and South America, we here revise the taxonomy of Guapinannus, describing 19 species as new (Guapinannus anaticulus, sp. n.; Guapinannus artus, sp. n.; Guapinannus auriculus, sp. n.; Guapinannus castigatus, sp. n.; Guapinannus clava, sp. n.; Guapinannus dispar, sp. n.; Guapinannus falcis, sp. n.; Guapinannus graziae, sp. n.; Guapinannus minutus, sp. n.; Guapinannus orbiculatus, sp. n.; Guapinannus plurilobus, sp. n.; Guapinannus policis, sp. n.; Guapinannus robustus, sp. n.; Guapinannus sinuosus, sp. n.; Guapinannus tatumbia, sp. n.; Guapinannus tenuis, sp. n.; Guapinannus tergus, sp. n.; Guapinannus trilobus, sp. n.; Guapinannus uncus, sp. n.). In addition, we provide photos of the female holotype of Guapinannus bierigi Wygodzinsky, 1951, SEM documentation for Guapinannus clava, sp. n., habitus photos and a map for all species, and line drawings of male genitalic features for all species for which males are known.